ABDURRAUF SINGKEL’S INSAN KAMIL CONCEPT TO ANSWER THE PROBLEM OF SEXUAL CONSENT, CHILDFREE, NATURE AND NURTURE IN URBAN SOCIETY - Ihsan, Nur Hadi; Sa'ari, Che Zarrina Binti; Sansayto, Tistigar; Indallah, Sayyid Muhammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2024)
This article aims to analyze Abdurrauf Singkel's concept of Insan Kamil to address the problems of sexual consent, childfree, and nature and nurture which frequently arise in urban society. These issues are a common phenomenon in contemporary urban society due to their materialistic lifestyle and the pursuit of worldly goals by denying their true nature (fitrah). Sufism's concept of